Generación, características básicas y principales efectos de las ondas de espín en sistemas magneto-cuánticos - Ferradas González, Kevin Renato (2023)
In the present work the generation process and the fundamental characteristics of_x000D_ the collective excitations, known as spin waves, in magneto-quantum particle sys tems, have been analyzed. From the Heisenberg hamiltonian, the fundamental sta te of the system where all the spins are completely aligned parallel to an external_x000D_ magnetic field was deduced. The spin-wave dispersion relation was calculated by_x000D_ applying the nearest-neighbor interaction approximation. The spontaneous magne tization and the specific heat of the Heisenberg ferromagnet at low temperatures_x000D_ were determined. It was found that: (i) the excited states are linear combinations_x000D_ of single spin-reduced states representing collective excitations, (ii) the quanta of_x000D_ spin waves (magnons) are bosonic in nature with spin equal to 1, (iii) the frequency_x000D_ of spin oscillations is proportional to the square of the wave vector, iv) using the_x000D_ Holstein-Primakoff transformations, the Heisenberg hamiltonian can be expressed_x000D_ as the sum of decoupled harmonic oscillators, v) the spontaneous magnetization_x000D_ and the specific heat vary with temperature according to raised to the 2/3